FOREGROUNDING AND INTERPRETATION - Achilov, Oybek (Журнал иностранных языков и лингвистики, 2023)
The studying of foregrounding and its interpretation is very actual to distinguish further information on cognitive science, therefore in this article, it has been analyzed and covered points interrelated to research cognitive semantics of a literary text with cognitive meaning.